Ideas for Action 2019 : Financing Sustainable Development - Mohieldin, Mahmoud; Petkoski, Djordjija (Washington, DC: World Bank, 2019)
Ideas for Action is a youth competition on initiatives to implement the Sustainable Development Goals launched in November 2014 by the World Bank Group and the Zicklin Center for Business Ethics Research at the Wharton School of the University of Pennsylvania. The 2019 winners (3 top teams, 4 runners-up, and 11 honorable mentions) were selected from more than 3,000 proposals submitted by more than 21,000 team members from 142 countries. This year witnessed an unparalleled level of growing recognition with a 50 percent increase in proposals over 2018. The winning proposals were selected through a rigorous selection process that judged the projects on depth and clarity, significance of impact, originality and creativity, and feasibility. The teams had to showcase a strong proposal that presented a potential for impact on a large number of people with a practical roadmap for implementation. In addition to young staff members, reviewers included executives from Firmenich, Flour Mills of Nigeria, the German–Brazilian Chamber of Commerce and Industry, PepsiCo, the Wharton School, and the World Bank Group. Other competition partners included the International Labour Organization, Hemofarm, the World Bank Group’s Youth to Youth Community (Y2Y) and Youth Summit, Knowledge @ Wharton, and the United Nations Youth Assembly. Youth participation in the 2030 Development Agenda is crucial. This initiative is a knowledge-sharing platform that empowers young professionals with the support and tools needed to engage in the conversation with leading professionals in the global development industry and the private sector. Through their use of technology—such as rainwater harvesting, reusable plastics, mobile apps, and devices—young people have ideas to make an exponential impact. The goal is to support truly workable and actionable results by connecting leading schools of finance and management with governments around the world to build partnerships that bolster these ideas into effective implementation. This book recognizes the incredible talent and spirit that these young people bring to the global development conversation.